Does age influence normal gastro-oesophageal reflux?. Issue 8 (August 1985) - Spence, R A; Collins, B J; Parks, T G; Love, A H
Abstract : Prolonged oesophageal pH monitoring is being used increasingly to detect abnormal gastro-oesophageal reflux. To assess the influence of age on normal reflux patterns, a group of 13 young asymptomatic subjects (mean age 22 years) was compared with a group of 14 middle aged asymptomatic subjects (mean age 49 years). An ambulatory system using a radiotelemetry capsule and a portable receiving system was used, oesophageal pH being recorded for at least 16 hours during an overnight hospital stay under standardised conditions. There was no significant difference in the duration or frequency of reflux episodes as defined by pH less than 5, less than 4, less than 3, or as a fall in pH of more than two units. It is concluded that it is an acceptable practice to use young volunteers to establish normal values in reflux studies of young and middle aged patients.